Impact of Microwave Assisted Heating on Hydrolytic Forced Degradation Study of Pharmaceuticals - N. Patel, Prutha; J. Mehta, Priti (Current Microwave Chemistry, 2017)
Background: Stress testing as an important segment in the process of getting drug to the market and are intended to reveal stability issues. Methods: In stress testing, it is mentioned to perform the task (hydrolytic or thermolytic degradation) at elevated temperature as and when required. Elevation in temperature by means of microwave irradiation has picked up lot of consideration owing to the in-core heating of the medium. Results: In stress testing of pharmaceuticals, degradation of drug can be achieved with in very short duration of time using microwave assisted heating compare to conventional heating. But at the same time it is essential to monitor and optimize parameters of microwave irradiation otherwise there are chances of false interpretation of the results. Conclusion: This review article is focused on the principle of microwave heating, types of microwave apparatus and use of microwave radiation for hydrolytic forced degradation studies of pharmaceuticals. It is tried to compare degradation profile of drug obtained by conventional heating and microwave heating.
Keywords: Comparative evaluation of conventional heating over microwave heating